Social Worker’s Experiences in a Case of Client’s Death in the Context of Wellbeing - Jolanta Buinevičienė; Laima Milkintaitė (Social Welfare: Interdisciplinary Approach)
The article analyzes the reactions of social workers after losing contact with the client, the psychological and spiritual experiences of the meaning of life and death, and the impact of the loss on the social worker’s life and wellbeing. The results of the research on the emotional distress of social workers after experiencing the client’s death are presented. The obtained results show that social workers confronted with the death experience similar reactions and emotional distress: shock, anxiety, guilt, self-loathing, concern, pity, sadness, helplessness, yearning, peace. Analyzing the data, the amplitude of the emotions experienced by social workers is compared with the ones most frequently presented in scientific sources, while the metaphors used in the informants’ stories are associated with intense emotional experiences and significance of the feelings experienced by social workers during the first reaction to the client loss. The social workers’ ability to act in difficult situations is presented. It includes planning, organization, cooperation and managerial skills in organizing funerals, knowledge in providing psychological support. The study has revealed that, according to the meaning reconstruction concept, the consistency of the person’s system of meanings is disrupted by the loss, and in trying to find meaning in the loss, the grieving person discovers other experiences.